2010
DOI: 10.1111/j.1744-7976.2010.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Adjustment of Irrigation Technology/Water Management in Western U.S. Agriculture: Toward a Sustainable Future

Abstract: Changing water demands induced through climate change and a growing biofuel energy sector throughout the western States are expected to increase pressures on the present allocation mechanisms for an increasingly scarce resource, raising uncertainty about the sustainability of irrigated agriculture in the West. In this paper, we first present the policy motivation for examining continued producer adoption of water conserving irrigation production systems as a foundation for providing a sustainable future for we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Adoption of water conserving technologies can decrease variance in net returns by allowing for higher output when applying the same quantity of water. In the western United States in 2003, 58 percent of irrigated acres used pressurized sprinkler or drip systems, and 40 percent of those systems were low‐pressure, water conserving systems (Schaible et al ). In contrast, in the Mexicali Valley over 95 percent of wheat and alfalfa farmers and 63 percent of cotton farmers use gravity‐flow systems (Carrillo‐Guerrero ).…”
Section: Farm Resilience and Risk Management Literaturementioning
confidence: 99%
“…Adoption of water conserving technologies can decrease variance in net returns by allowing for higher output when applying the same quantity of water. In the western United States in 2003, 58 percent of irrigated acres used pressurized sprinkler or drip systems, and 40 percent of those systems were low‐pressure, water conserving systems (Schaible et al ). In contrast, in the Mexicali Valley over 95 percent of wheat and alfalfa farmers and 63 percent of cotton farmers use gravity‐flow systems (Carrillo‐Guerrero ).…”
Section: Farm Resilience and Risk Management Literaturementioning
confidence: 99%
“…() and Schaible et al. () have demonstrated the need to differentiate between consumptive use and applied water. Use of applied water over‐estimates the benefits of groundwater management.…”
Section: Model Specificationmentioning
confidence: 99%
“…Water that is consumptively used nets out application losses to runoff, evaporation and recharge. Other studies including , and Schaible et al (2010) have demonstrated the need to differentiate between consumptive use and applied water. Use of applied water over-estimates the benefits of groundwater management.…”
Section: Dynamic Economic Sub-modelmentioning
confidence: 99%
“…Another relevant characteristic of groundwater supply is that current use can impose substantial future costs. Schaible et al (2010) specify a dynamic model to evaluate factors determining water use and efficiency that endogenizes groundwater application, technology adoption, and user cost. In many jurisdictions, there are increasingly stringent in-stream flow requirements to maintain water quality for indigenous aquatic species and to maintain river deltas and flood plains.…”
Section: Water Supply and Demandmentioning
confidence: 99%